Pengaruh Pendapatan dan Biaya Operasional terhadap Laba Bersih di PT PLN Unit Induk Distribusi Jawa Barat - Rifana, Nabila; Nur'aeni, Nur'aeni (Ma'soem University, 2025)
The purpose of this research is to analyze the effect of Revenue and Operating Expenses on Net Profit at PT PLN Persero for the 2020-2024 period, both partially and simultaneously. The research object is the financial statements of PT PLN Persero. This study employs a quantitative method with an associative approach. The data used is secondary data, collected through and documentation techniques. The sampling technique applied is purposive sampling, with the population comprising all financial statements of PT PLN Persero and samples in the form of semester financial reports for the 2020-2024 period. The data analysis used is multiple correlation, multiple regression, coefficient of determination, t test and f test. The results of this study indicate that there is no significant effect of Revenue on Net Profit based on the t-test, where the calculated t-value is less than the table value (1.51381 < 1.8595). There is an effect of Operating Costs on Net Profit, where the calculated t-value is greater than the table value (1.9465 > 1.8595). Meanwhile, the F-test results show that simultaneously Revenue and Operating Costs do not have a significant effect on Net Profit, as the calculated F-value is less than the table value (0.3444 < 4.74).